Assessment of Clindamycin and Erythromycin Resistance, and Inducible Clindamycin Resistance in Streptococcus Group B Isolated from Urinary Samples of Outpatient Women in Tehran - Frouhesh-Tehrani, Homa; Ashrafi-Hafez, Asghar; Sharifi, Zohreh; Farahzadi, Hossein (Novelty in Biomedicine, 2015)
Background: Streptococcus group B (GBS) or Streptococcus agalactiae is typically associated with neonatal disease and infection in pregnant women. Mortality of GBS sepsis in neonates is over 50% and is particularly high in preterm infants. GBS also causes invasive infection in pregnant and non-pregnant women including urinary tract infection (UTI). Penicillin-derived antibiotics remained as choice drugs for treatment of GBS infection; however, Erythromycin and Clindamycin are useful in cases of allergic to Penicillin. The aim of this study was to investigate the resistance to Erythromycin and Clindamycin, especially inducible Clindamycin resistance, in GBS isolated from urinary samples of women who attended medical offices in Tehran, Iran. Materials and Methods: This study was conducted on 5000 urine samples from Jan. 2011 to Oct. 2012 that 104 GBS were isolated. The isolates were identified as GBS using laboratory criteria. Antimicrobial susceptibility test was done by Erythromycin disk 15µg and Clindamycin disk 2µg for observation inducible resistant D-zone test by double-disk diffusion method with Erythromycin and adjacent Clindamycin. Results: Among the 5000 urine samples 104 (2.08%) were Beta hemolytic GBS. Of the 104 isolated GBS, 22 (21.2%) were resistance, 24 (23%) were intermediate, and 58 (55.8%) were susceptible to Erythromycin; however, 24 (23%) were resistance, 5 (4.8%) were intermediate, and 75 (72.2%) were susceptible to Clindamycin. Of the 22 Erythromycin-resistant isolates, 10 (9.5% in total GBS isolated) displayed the D zone; it means they have inducible Erythromycin resistant to Clindamycin. Conclusion: Various studies in other countries report lower rates of inducible Clindamycin resistance; it indicates the use of more macrolides in the treatment of UTI.